1983
DOI: 10.1007/bf00325910
|View full text |Cite
|
Sign up to set email alerts
|

Construction and use of pyr::lac fusion strains to study regulation of pyrimidine biosynthesis in Salmonella typhimurium

Abstract: The technique developed by Rosenfeld and Brenchley [J Bacteriol 144, 848-851 (1980)] has been used to introduce Mu d1 (Apr lac) into Salmonella typhimurium for purposes of constructing pyr::lac fusion strains. A stable pyrB::lac fusion mutant was subsequently derived and used for the genetic characterization of the pyrB gene. The direction of transcription of pyrB was determined to be counterclockwise on the S. typhimurium linkage map and argI was shown to be located clockwise of pyrB. Mutants altered in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Transfer of an out (dctA) mutation to a usp strain was selected by plating on the same basic medium, but with the addition of FOA. Methods for transposon technology with Tn10 were as previously reported (27). Conjugations were carried out as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of an out (dctA) mutation to a usp strain was selected by plating on the same basic medium, but with the addition of FOA. Methods for transposon technology with Tn10 were as previously reported (27). Conjugations were carried out as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, 5-fluoroorotate (FOA) is a potent growth inhibitor in glycerol minimal medium and has been employed for the selection of pyrH (UMP kinase) mutants of both S. typhimurium (40) and E. coli (15). It has been observed that orotate is growth rate limiting for carAB and pyrBI mutants in a concentration-dependent manner, and culturing cells at varying orotate concentrations has been used as a means to establish partial pyrimidine starvation for purposes of studying the impact of pyrimidine nucleotide limitation on specific gene expression and general aspects of macromolecular synthesis (3,5,27,36,38). In contrast, reducing the concentration of uracil serves to lower only the growth yield, not the growth rate (36), and indicates that the transport of orotate into the cell represents a rate-limiting step.…”
mentioning
confidence: 99%
“…The composition of the minimal medium has been reported [14]. The complex media, nutrient broth and L broth, were prepared as described [I 51.…”
Section: Media and Culture Methodsmentioning
confidence: 99%
“…Chromosomal DNA from strain MLX2, a previously characterized pyrB regulatory mutant derived from strain MLXI [14], was digested with EcoRI and cloned into the EcoRI site of pGM5. Ligation of the EcoRI site in lac2 of the donor pyrB: :MudlX DNA in the correct orientation produces a construct with an intact lacZ, the expression of which is governed by the pyrB regulatory region.…”
Section: Pstlmentioning
confidence: 99%
“…Hfr derivatives of the pyr-lac+ fusion strains which transfer their chromosome in the direction of pyr gene transcription were constructed by forcing the F'tsll4 lac' zzf-21: :TnlO episome to integrate into the chromosome by lac homology, essentially as described by Michaels and Kelln [27]. Equal volumes of the Salmonella typhimurium strain KP1938 (trp,cys) containing the F'lac' episome and the recipient fusion strains were mixed, incubated at 30 "C for 30min and plated on minimal agar with lactose (0.1%) as carbon source and containing tetracycline (10 pg/ml).…”
Section: Determination Of Direction Of Pyr Gene Transcriptionmentioning
confidence: 99%